2019
DOI: 10.3389/fbioe.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Corneal Biomechanical Behavior in-vivo for Healthy Eyes Using CorVis ST Tonometry: Stress-Strain Index

Abstract: Purpose: This study aims to introduce and clinically validate a new algorithm that can determine the biomechanical properties of the human cornea in vivo . Methods: A parametric study was conducted involving representative finite element models of human ocular globes with wide ranges of geometries and material biomechanical behavior. The models were subjected to different levels of intraocular pressure (IOP) and the action of external air puff produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
178
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(198 citation statements)
references
References 35 publications
14
178
1
5
Order By: Relevance
“…It was shown as an ideal method to estimate the mechanical properties of corneal tissue material. The distribution of SSI in Italian and Brazilian populations has been reported by previous studies and SSI was found to be signi cantly affected by age 8 . Chua observed that a lower corneal hysteresis (CH) in Chinese than Indians, suggesting that corneal biomechanics may be varies among different populations 11 .…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…It was shown as an ideal method to estimate the mechanical properties of corneal tissue material. The distribution of SSI in Italian and Brazilian populations has been reported by previous studies and SSI was found to be signi cantly affected by age 8 . Chua observed that a lower corneal hysteresis (CH) in Chinese than Indians, suggesting that corneal biomechanics may be varies among different populations 11 .…”
Section: Introductionsupporting
confidence: 70%
“…Besides IOP, previous studies have shown that, parameters of corneal biomechanics in vivo were mostly affected by bIOP such as de ection area at the highest concavity and de ection amplitude (HC DefArea and HC DefA), SP -A1 38 CH and CRF 39 . However, SSI based on nite element (FE) numerical modeling simulating the effects of Corvis ST air puff and bIOP to predict of corneal behavior and excluded the in uence of bIOP, indicating that this is an ideal method for in vivo measurement of corneal tissue material stiffness 8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Auch Finite-Elemente-Simulationen wurden durchgeführt, um den Zusammenhang zwischen Augeninnendruck und kornealer Biomechanik zu analysieren [6]. Diese Grundlagenforschung führte zur Entwicklung neuer biomechanischer Parameter, die direkt mit der Hornhautsteifigkeit [7] sowie dem Spannungs-Dehnungs-Verhalten der Hornhaut [8] zusammenhängen. Diese Parameter zeigten alle signifikante Unterschiede zwischen gesunden Augen und Augen mit Keratokonus [9].…”
Section: Introductionunclassified